2016
DOI: 10.1186/s40064-016-1933-y
|View full text |Cite
|
Sign up to set email alerts
|

Association of high-sensitivity C-reactive protein and uric acid with the metabolic syndrome components

Abstract: Metabolic syndrome (MetS) has been found to be associated with inflammatory molecules. This study was conducted among 125 MetS patients at B P Koirala Institute of Health Sciences, Dharan, Nepal to find an association of high-sensitivity C-reactive protein (hs-CRP) and serum uric acid with MetS components. Anthropometric measurements, blood pressure, medical history and blood samples were taken. Estimation of hs-CRP, serum uric acid, blood glucose, triglyceride and high density lipoprotein (HDL) cholesterol wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…Among the factors associated with hyperuricemia were increased CRP levels. It was shown that increased CRP serum concentration is found in patients with MetS, with obesity being the major determinant of CRP levels [61][62][63]. This is explained by the production of inflammatory cytokines such as interleukin-6 (IL-6) in the adipose tissue [63].…”
Section: Discussionmentioning
confidence: 99%
“…Among the factors associated with hyperuricemia were increased CRP levels. It was shown that increased CRP serum concentration is found in patients with MetS, with obesity being the major determinant of CRP levels [61][62][63]. This is explained by the production of inflammatory cytokines such as interleukin-6 (IL-6) in the adipose tissue [63].…”
Section: Discussionmentioning
confidence: 99%
“…In a study in Chinese, the prevalence of MetS increased with rise in serum UA levels and MetS component number presented a significantly increasing trend across serum UA quartiles in both sexes. Additionally, participants with HUA or higher serum UA levels were at significantly higher ORs for MetS and its related components including abdominal obesity, hypertension, hyperglycemia, and low HDL cholesterol [ 9 , 10 ]. These previous studies suggested that serum UA levels may be a useful predictor for metabolic disorders.…”
Section: Introductionmentioning
confidence: 99%
“…It is of note that the increase in the level of uric acid in the AP2 patients was correlated with an increase in the CRP level, and with WG. Metabolic syndrome components, including WG, have been previously associated with high levels of CRP and uric acid [ 42 ], while CRP is highly predictive of subsequent risk of cardiovascular events and DM in apparently healthy men and women [ 43 ]. The correlation in our study of uric acid and CRP with administration of AP2 drugs supports our previous suggestion that this group of SGAPs is responsible for extensive metabolic and inflammatory complications [ 1 , 42 , 44 ].…”
Section: Discussionmentioning
confidence: 99%